2024
DOI: 10.3389/fnut.2024.1299810
|View full text |Cite
|
Sign up to set email alerts
|

Nisin and ε-polylysine combined treatment enhances quality of fresh-cut jackfruit at refrigerated storage

Liping Zeng,
Aiping Fan,
Guangming Yang
et al.

Abstract: This study investigated the effects of nisin combined with ε-polylysine on microorganisms and the refrigerated quality of fresh-cut jackfruit. After being treated with distilled water (control), nisin (0.5 g/L), ε-polylysine (0.5 g/L), and the combination of nisin (0.1 g/L) and ε-polylysine (0.4 g/L), microporous modified atmosphere packaging (MMAP) was carried out and stored at 10 ± 1°C for 8 days. The microorganisms and physicochemical indexes were measured every 2 days during storage. The results indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Therefore, the search for effective techniques to alleviate browning and inhibit the growth of microorganisms in potatoes has become a major concern. Many studies have confirmed that the combined treatment was more efficient in maintaining the quality of fresh-cut products than individual treatments [25,33]. In addition, the use of RSM analysis to optimize combined treatment conditions to maintain the quality of fresh-cut products has been demonstrated nowadays on fresh-cut oranges [34] and fresh-cut apples [35].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the search for effective techniques to alleviate browning and inhibit the growth of microorganisms in potatoes has become a major concern. Many studies have confirmed that the combined treatment was more efficient in maintaining the quality of fresh-cut products than individual treatments [25,33]. In addition, the use of RSM analysis to optimize combined treatment conditions to maintain the quality of fresh-cut products has been demonstrated nowadays on fresh-cut oranges [34] and fresh-cut apples [35].…”
Section: Discussionmentioning
confidence: 99%